JWST/MIRI Detection of Suprathermal OH Rotational Emissions: Probing the Dissociation of the Water by Lyα Photons near the Protostar HOPS 370 - David A. Neufeld; P. Manoj; Himanshu Tyagi; Mayank Narang; Dan M. Watson; S. Thomas Megeath; Ewine F. Van Dishoeck; Robert A. Gutermuth; Thomas Stanke; Yao-Lun Yang; Adam E. Rubinstein; Guillem Anglada; et al. (The Astrophysical Journal Letters, 2024)
Using the MIRI medium-resolution spectrometer on JWST, we have detected pure rotational, suprathermal OH emissions from the vicinity of the intermediate-mass protostar HOPS 370 (OMC2/FIR3). These emissions are observed from shocked knots in a jet/outflow and originate in states of rotational quantum number as high as 46 that possess excitation energies as large as E _U / k = 4.65 × 10 ^4 K. The relative strengths of the observed OH lines provide a powerful diagnostic of the ultraviolet radiation field in a heavily extinguished region ( A _V ∼ 10–20) where direct UV observations are impossible. To high precision, the OH line strengths are consistent with a picture in which the suprathermal OH states are populated following the photodissociation of water in its $\tilde{B}-X$ band by ultraviolet radiation produced by fast (∼80 km s ^−1 ) shocks along the jet. The observed dominance of emission from symmetric ( $A^{′} $ ) OH states over that from antisymmetric ( A ″) states provides a distinctive signature of this particular population mechanism. Moreover, the variation of intensity with rotational quantum number suggests specifically that Ly α radiation is responsible for the photodissociation of water, an alternative model with photodissociation by a 10 ^4 K blackbody being disfavored at a high level of significance. Using measurements of the Br α flux to estimate the Ly α production rate, we find that ∼4% of the Ly α photons are absorbed by water. Combined with direct measurements of water emissions in the ν _2 = 1 − 0 band, the OH observations promise to provide key constraints on future models for the diffusion of Ly α photons in the vicinity of a shock front.